Estimating Primary Production of Picophytoplankton Using the Carbon-Based Ocean Productivity Model: A Preliminary Study - Liang, Yantao; Zhang, Yongyu; Wang, Nannan; Luo, Tingwei; Zhang, Yao; Rivkin, Richard B. (Frontiers in Microbiology, 2017)
Picophytoplankton are acknowledged to contribute significantly to primary production in the ocean while now the method to measure primary production of picophytoplankton at large scales is not yet well established. Although the traditional 14C method and new technologies based on the use of stable isotopes (e.g. 13C) can be employed to accurately measure in situ primary production of picophytoplankton, the time-consuming and labor-intensive shortage of these methods constrain their application in a survey on large spatiotemporal scales. To overcome this shortage, a modified carbon-based ocean productivity model (CbPM) is proposed for estimating the primary production of picophytoplankton whose principle is based on the group-specific abundance, cellular carbon conversion factor and temperature derived growth rate of picophytoplankton. Comparative analysis showed that the estimated primary production of picophytoplankton using CbPM method is significantly and positively related (r2= 0.53, P<0.001, n= 171) to the measured 14C uptake. This significant relationship suggests that CbPM has the potential to estimate the primary production of picophytoplankton over large spatial and temporal scales. Currently this model application may be limited by the use of invariant cellular carbon conversion factor and the relatively small data sets to validate the model which may introduce some uncertainties and biases. Model performance will be improved by the use of variable conversion factors and the larger data sets representing diverse growth conditions. Finally, we apply the CbPM-based model on the collected data during four cruises in the Bohai Sea in 2005. Model-estimated primary production of picophytoplankton ranged from 0.1 to 11.9, 29.9 to 432.8, 5.5 to 214.9 and 2.4 to 65.8 mg C m–2 d–1 during March, June, September and December, respectively. This study shed light on the estimation of global primary production of picophytoplankton using carbon-based production model.